System engineering approach for assisting physical-ly challenged and geriatric persons - Shankar Rao, R. Gowri; Rayaguru, N.K.; Kumar Thakur, Sunil (International Journal of Engineering and Technology, 2017)
The embedded application aims to provide the needful for the physically challenged people those who find difficulties in taking care of themselves in their day to day activities. A small survey has been undertaken at Cuddalore and Chennai of Tamilnadu regarding the problems faced by old aged physically challenged people. From their discussions and observations, it has been analyzed that old aged people have chronic disorders such as hearing, vision impairment, balance disorder, health disabilities etc. The microcontroller based data acquisition system is used to develop suitable applications such as medicine reminder system, guiding the location and object for blind people.
Keywords: Microcontroller; RFID Module; Wireless Protocol; GSM Module; SMS.